Mycobacterial diseases and antitumour necrosis factor therapy in USA. Issue 1 (20th April 2012) - Winthrop, KL; Baxter, R; Liu, L; Varley, CD; Curtis, JR; Baddley, JW; McFarland, B; Austin, D; Radcliffe, L; Suhler, EB; Choi, D; Rosenbaum, JT; et al.
Abstract : Objective: In North America, tuberculosis and nontuberculous mycobacterial (NTM) disease rates associated with antitumour necrosis factor α (anti-TNFα) therapy are unknown. Methods: At Kaiser Permanente Northern California, the authors searched automated pharmacy records to identify inflammatory disease patients who received anti-TNF therapy during 2000–2008 and used validated electronic search algorithms to identify NTM and tuberculosis cases occurring during anti-TNF drug exposure. Results: Of 8418 anti-TNF users identified, 60% had rheumatoid arthritis (RA). Among anti-TNF users, 18 developed NTM and 16 tuberculosis after drug start. Anti-TNF associated rates of NTM and tuberculosis were 74 (95% CI: 37 to 111) and 49 (95% CI: 18 to 79) per 100 000 person-years, respectively. Rates (per 100, 000 person-years) for NTM and tuberculosis respectively for etanercept were 35 (95% CI: 1 to 69) and 17 (95% CI: 0 to 41); infliximab, 116 (95% CI: 30 to 203) and 83 (95% CI: 10 to 156); and adalimumab, 122 (95% CI: 3 to 241) and 91 (95% CI: 19 to 267). Background rates for NTM and tuberculosis in unexposed RA-patients were 19.2 (14.2 to 25.0) and 8.7 (5.3 to 13.2), and in the general population were 4.1 (95% CI 3.9 to 4.4) and 2.8 (95% CI 2.6 to 3.0) per 100, 000 person-years. Among anti-TNF users, compared with uninfected individuals, NTM case-patients were older (median age 68 vs 50 years, p<0.01) and more likely to have RA (100% vs 60%, p<0.01); whereas, tuberculosis case-patients were more likely to have diabetes (37% vs 16%, p=0.02) or chronic renal disease (25% vs 6%, p=0.02). Conclusions: Among anti-TNF users in USA, mycobacterial disease rates are elevated, and NTM is associated with RA.